Patrick O’Neill. Transforming Kafka: Translation Effects. Toronto: U of Toronto P, 2014. 222 pp. - Robert Lemon (Studies in 20th & 21st Century Literature, 2016)
Review of Patrick O’Neill. Transforming Kafka: Translation Effects. Toronto: U of Toronto P, 2014. 222 pp.
Keywords: Franz Kafka; literary translation